Melioidosis: a localized osteomyelitis in a cat - Lim, May Lyn; Ismail, S. S.; Rahman, N.; Watanabe, M. (Veterinary Association Malaysia, 2015)
Melioidosis is a zoonotic disease as a result of infection by Burkholderia pseudomallei. It is of significant public health concern due to its ubiquitous nature with high morbidity and mortality in humans and animals. In cats, the disease is usually reported with abscess formation in lung, liver and spleen, however, isolated articular melioidosis is rare. A 1-year-old, a female Domestic Shorthair cat was presented to University Veterinary Hospital, Universiti Putra Malaysia (UVH-UPM) with swollen right elbow and non weight bearing lameness of the right forelimb. Physical examination revealed pyrexia, soft tissue swelling and pain upon palpation of the right elbow joint. Radiographs of the right forelimb revealed osteolysis at the distal third of the humerus and proximal radius and ulna, cortical thinning at the olecranon and soft tissue swelling around the elbow joint. Bacterial culture of the joint fluid revealed positive growth for Burkholderia pseudomallei. Unfortunately, the owner opted to euthanise the cat citing personal reasons. Upon necropsy, there was presence of multiple caseous nodules within the right elbow joint cavity only and none of the other limbs, lung, spleen and liver was affected. It is important for veterinarian to be aware of septic arthritis and osteomyelitis form of melioidosis.